Teoria da norma tributária imunizante - Luz, Gyordano Kelton Alves (2010)
The purpose of this study is to analyze the tax rule immunizing with the scope to reach the MIRIM - Irreducible Minimum Immunity. It is also studying RMIT - Rule-tax Impact Matrix creating Paulo de Barros Carvalho from two perspectives: static and dynamic. The work is innovative, because they are applied the lessons of Quantum Physics and the Theory of Relativity to reach MIRIM. Static perspective (application of Quantum Physics): We started a study stating that there are two types of rules: the legal and not legal. Specifically legal norms have a complex process of interpretation and application which is summarized in two "pathways generators": the meaning and normative. After hours of discussions we realized that the atom and the rule of law have a tax structure. Atoms are composed of quarks (Up, Down, Strange, Charmed, Bottom and Top) and legal tax provision consists of the criteria of RMIT (material, spatial, temporal, quantitative and staff). Deepening the comparison comes on the atomic elements (electrons, protons and neutrons) and the modal deontic normative (prohibited, obligatory and permitted). The combination of all atomic elements give rise to a final positive or negative charge. In the case of deontic modals which will be positive or negative is the approach to treatment of the subjects of tax relationship. Dynamic approach (application of the Theory of Relativity): In that instant is studied the influence of space and time. The space / time is described in the protasis normative, more specifically in the criterion space and time criterion. Applying the precepts of the theory of relativity, it was concluded the necessity of joining these two criteria, because a tenet of relativity is that time and space do not separate, thus creating a feature called quantum / relative. Therefore, we propose a "new" as well as RMIT complies with the precepts of the theory of relativity is thus more balanced, with two criteria in history (material and quantum / relative) and the consequent two criteria (quantitative and personal ). Leaving the following legal premise: if every legal tax rule, being a man of building (object of the cultural world) has a structure, so the tax rule immunizing also have to have a structure. That is the premise that underpins the work. The tax rule is divided into: a standard of conduct and standard structure. In the first applies to RMIT and in the second applies the MIRIM. The MIRIM is in line with the teachings of quantum physics, because there are two criteria in the protasis normative (legal and quantum well / relative) and two criteria in apodosei normative (subjective rights and legal duty). The MIRIM complies with the precepts of the Theory of Relativity, as space and time form a single normative criterion contained in the protasis. Finally, not only staying in theory will apply the standards in some MIRIM tax immunity